Insights into the Kinetic Compensation Effects and Kinetic Parameters during Gasification of Low-Rank Coal Char - Jena, Manoj Kumar (Curtin University, 2022)
Gasification technologies are the primary route for the effective utilization of low-rank coals. This thesis presents an in-depth analysis of kinetic compensation effects with the fundamental understanding of change in apparent kinetic parameters during the gasification of low-rank coal char in different gasifying environments. The mechanistic insights into char gasification were obtained by investigating the kinetic compensation effects of char consumption and product gas formations. The findings will add value to gasification technology.